PREDIKSI UMUR LAYANAN PERKERASAN JALAN AKIBAT BEBAN MUATAN LEBIH KENDARAAN ( STUDI KASUS RUAS JALAN DURI – MINAS) - Abu Bakar; Muhammad Idham; Indriyani Puluhulawa (Racic : Rab Construction Research, 2018)
Overloading is a condition of a vehicle's axle load exceeding the standard load used on the pavement design assumptions or the number of operational paths before the age of the plan is reached, or often referred to as premature deterioration. and the consequence of overloading of the road will decrease the service life of the road. The axis load allowed to pass through the road is 8 tons but in fact the field of passing vehicles exceeds the limit allowed by overloaded trucks. This is evidenced by the Department of Public Works of Riau Province states that 45% of damage caused by vehicle excess burden. The purpose of the research undertaken, namely to determine the reduced service life of the road from the design life that has been determined due to vehicle load. The method obtained is by calculating the ESAL cumulative standard and ESAL existing to get Traffic Design (ESAL). From the analysis of Traffic Design (ESAL), the age of pavement is expected to end in the 7th year since the road increase or there is a reduction of 3 years from the age of the 10 year plan and the expected reduction in the remaining age of 52.60% since the road repair has ended.